2016
DOI: 10.1002/pssc.201600095
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nb doping on the structural, morphological, optical and electrical properties of RF magnetron sputtered In2O3 nanostructured films

Abstract: Undoped and niobium (Nb) doped indium oxide (In2O3) thin films are prepared by radio frequency magnetron sputtering technique. The effect of Nb on the structural, morphological, optical and electrical properties of In2O3films are analyzed using techniques such as X‐ray diffraction (XRD), micro‐Raman spectroscopy, X‐ray photoelectron spectroscopy, atomic force microscopy, field emission scanning electron microscopy (FESEM), energy dispersive X‐ray spectroscopy, UV–visible spectroscopy, spectroscopic ellipsometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The In 3d 3/2 and In 3d 5/2 peaks were obtained at 451.5 and 443.97 eV in Au/ In 2 O 3 , respectively (Figure S6b), which is related to the characteristic peaks of In 3+ . 21,22 After SAM modification, the In 3d peaks all shifted to a higher energy side in some extent, indicating that the loading of SAMs changed the chemical environment around the indium atom. 23 In addition, C−Si−O peaks could be detected in the SAM-loaded Au/In 2 O 3 NF samples in contrast to the pristine Au/In 2 O 3 NF sample (Figure S6c), demonstrating the successful and firm surface modification of SAMs via Si−O−In bonds via the hydrolysis reaction (Figure S6d).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The In 3d 3/2 and In 3d 5/2 peaks were obtained at 451.5 and 443.97 eV in Au/ In 2 O 3 , respectively (Figure S6b), which is related to the characteristic peaks of In 3+ . 21,22 After SAM modification, the In 3d peaks all shifted to a higher energy side in some extent, indicating that the loading of SAMs changed the chemical environment around the indium atom. 23 In addition, C−Si−O peaks could be detected in the SAM-loaded Au/In 2 O 3 NF samples in contrast to the pristine Au/In 2 O 3 NF sample (Figure S6c), demonstrating the successful and firm surface modification of SAMs via Si−O−In bonds via the hydrolysis reaction (Figure S6d).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The tin donor was activated by crystallization due to the increase in thickness, as indicated in Figure 7, but not due to the substrate heating or annealing treatment. For a thickness less than d c , a moderate doping ratio was required in order to obtain higher electrical conductivity, seemly owing to the formation of energetically favorable V O -In i and V O -Sn In proposed by Tang et al [17] because too high a doping ratio would lead to lower carrier concentration and a lower doping ratio to more tin substitution inactivated. Apparently, the trend of electrical resistivity was coherent with the conversion from an amorphous to a crystalline state.…”
Section: Discussionmentioning
confidence: 99%
“…However, only Yang et al reported [15] that even lower resistivity could be obtained by sputtering ITO ceramic targets with doping metallic tin via co-sputtering. For the convenience of ITO target production, tin is still the favorite doping element although other doping elements have been reported already, e.g., Ti [16], Nb [17], Si [4], and H [18]. In addition, ITO films with thin thickness, i.e., less than 50 nm are of great technological importance in many applications, such as touch panels [7], which is quite different from the thicker ITO (several hundreds of nanometers) on glass for de-icing.…”
Section: Introductionmentioning
confidence: 99%
“…Photocatalytic water splitting hydrogen evolution converts endless solar energy to clean and environmentally friendly hydrogen fuel, thus becoming an impressive strategy in addressing the problems of both energy and environment. In 2 O 3 , as a well-known moderate band gap semiconductor (2.8 eV), possesses appropriate energy band structure, easily regulated morphology, low toxicity, and good stability and thus has received extensive attention in many areas. Although In 2 O 3 with different morphologies, such as In 2 O 3 nanorods, , microspheres, mesoporous films, nanowires, , and microflowers (MFs) assembled with nanosheets, have been studied as photocatalysts, their photocatalytic performances for hydrogen evolution are still very poor because of the limited absorption of solar light and the serious recombination of charge carriers. , Therefore, it is very important to seek effective strategies to solve these two main problems simultaneously for obtaining novel In 2 O 3 -based photocatalysts with high photocatalytic efficiency.…”
Section: Introductionmentioning
confidence: 99%